KEMAMPUAN BERBICARA SISWA KELAS XI A SMAN 10 KUPANG MENYAMPAIKAN ARGUMEN DALAM KELAS MELALUI PENERAPAN METODE DEBAT - Yulvin Fu’a; Labu Djuli; Margareta P. E. Djokaho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study focuses on analyzing and describing in detail the speaking ability of eleventh-grade students at SMA Negeri 10 Kupang, specifically in the context of presenting arguments in the classroom through the implementation of the debate method. Speaking skills, particularly in arguing, represent an essential competence that students must master in modern language learning. The selection of the debate method as the primary learning instrument is based on its proven effectiveness in creating a dynamic, communicative, and interactive learning atmosphere. Through the debate mechanism, students are not only required to speak up bravely when expressing opinions in public, but are also encouraged to sharpen their critical thinking skills, process supporting facts, and respond to opponents' ideas with logical and structured rebuttals. Methodologically, this study applies a descriptive qualitative approach to provide an objective, comprehensive, and detailed overview of students' rhetorical performance and argument formulation in the classroom. The theoretical foundation underpinning this research combines two main pillars: speaking theory and cognitive learning theory. Integrating these two theories aims to map not only external linguistic aspects—such as fluency, grammar usage, and articulation—but also students' internal cognitive processes in constructing reasoning structures and scientific thinking frameworks when defending arguments before an audience. The data collection and comprehensive analysis were conducted on 25 students of Class XI A at SMA Negeri 10 Kupang based on seven measurable indicators of speaking skills. Empirical evaluation results revealed variations in students' speaking abilities across four main performance categories: Very Good (90–100): A total of 7 students (28%) achieved highly satisfying performance within this highest score range. Good (80–89): This group includes 5 students (20%) who demonstrated solid mastery of argumentation. Fair (75–79): There were 3 students (12%) whose scores fell right at or slightly above the passing threshold. Poor (<75): A total of 10 students (40%) remained in this category as they had not met the established qualification criteria. Overall, these findings conclude that the speaking ability of Class XI A students at SMA Negeri 10 Kupang in presenting arguments through the debate method can generally be categorized as good, with a learning mastery percentage reaching 60%. Nevertheless, the fact that 40% of the students have not reached the Minimum Mastery Criterion (MMC) of 75 highlights a real challenge in the learning process. This empirical evidence underscores the importance of continuous instructional evaluation, refined individual mentoring techniques, and the implementation of more inclusive teaching strategies so that all students can evenly optimize their oral communication potential and critical reasoning skills. Overall, these findings conclude that the speaking ability of Class XI A students at SMA Negeri 10 Kupang in presenting arguments through the debate method can generally be categorized as good, with a learning mastery percentage reaching 60%. Nevertheless, the fact that 40% of the students have not reached the Minimum Mastery Criterion (MMC) of 75 highlights a real challenge in the learning process. This empirical evidence underscores the importance of continuous instructional evaluation, refined individual mentoring techniques, and the implementation of more inclusive teaching strategies so that all students can evenly optimize their oral communication potential and critical reasoning skills.